Goddess Girls AMPHITRITE THE BUBBLY - Holub Joan; Suzanne Williams (New York Joan Holub, 2005)
focuses on friendship, navigating school life, and developing their divine skills
Keywords: of Nepal, a tradition where a young, pre-pubescent girl from the Newar Buddhist Shakya community is worshipped as the earthly manifestation of divine female energy (Shakti), specifically the goddess Taleju; associated with the upbringing, protection, or archetypes of girls and young women, is complex, often reflecting a blend of nurturing, fierce protection, and sometimes chaotic, human-like, or contradictory behavior